2014
DOI: 10.7441/joc.2014.04.03
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Small and Medium Entrepreneurship in the Czech Republic

Abstract: This paper deals with small and medium enterprises in relation to the attitudes perceived by business owners in their immediate neighbourhood, society, in relation to banks and the government. The key question is the difference between entrepreneurs who started their businesses voluntarily and those who entered the business out of necessity. The majority of governmental policies, including Czech policies, focus more on the questions of financial support, however the support of entrepreneurs can be broader and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 23 publications
2
21
0
1
Order By: Relevance
“…Baštová et al [65] and Dvouletý and Mareš [66] further demonstrated that the highest density of registered businesses (self-employed individuals and business companies) can be found in the capital Prague, which is expected as the capital is the economic and political centre of the country. Other regional scholars [67][68][69][70][71][72] have highlighted the differences between engagement in entrepreneurship and self-employment across the Czech regions, and they further point out that the activity is most densely concentrated around larger towns and cities. It is also well known that the Czech business activity consists mainly of self-employed individuals [73,74].…”
Section: Entrepreneurial Activity In the Czech Republicmentioning
confidence: 99%
“…Baštová et al [65] and Dvouletý and Mareš [66] further demonstrated that the highest density of registered businesses (self-employed individuals and business companies) can be found in the capital Prague, which is expected as the capital is the economic and political centre of the country. Other regional scholars [67][68][69][70][71][72] have highlighted the differences between engagement in entrepreneurship and self-employment across the Czech regions, and they further point out that the activity is most densely concentrated around larger towns and cities. It is also well known that the Czech business activity consists mainly of self-employed individuals [73,74].…”
Section: Entrepreneurial Activity In the Czech Republicmentioning
confidence: 99%
“…This is caused mainly by historical and cultural reasons. However, the entrepreneurial environment and access to entrepreneurship for younger generations is gradually changing to the better (Smékalová et al, 2014). As a result, it is not easy to be competitive on the market nowadays.…”
Section: Theoretical Aspects Of Organizational Changesmentioning
confidence: 99%
“…It is strongly dependent on individuals and particularly on their decision about establishing a new entrepreneurial unit (Smékalová et al, 2014). One of the most important preconditions for their success followed by a positive impact on the performance characteristics of the economy as a whole is a friendly environment and perception of their business activities accompanying most stages of the company´s existence -its foundation, growth and stabilization, and eventually remediation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%